2018
DOI: 10.7172/1733-9758.2018.27.13
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corporate Governance on the Value of Enterprises

Abstract: Wspó czesne realia ycia gospodarczego ka spojrze na funkcjonowanie przedsi biorstwa przez pryzmat nie tylko podstawowego celu, jakim jest d enie do maksymalizacji zysku, ale z uwzgl dnieniem przy jego wypracowaniu potrzeb szerszej grupy interesariuszy. Dlatego coraz cz ciej przy dokonywaniu pomiaru warto ci przedsi biorstwa uwzgl dnia si aspekty jako ciowe, które wp ywaj na efektywno funkcjonowania przedsi biorstwa, jak równie na jego wycen . Do takich w a nie elementów zalicza si mechanizmy corporate governan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…According to the research of Luo et al (2016) which explained that to identify high-quality companies and lowquality companies were 92.16 percent and 93.75 percent, respectively, which indicated that the model has realized good predictions. While research on Wierzbicka (2018) with her research about these elements, they included corporate governance mechanisms. The basic role associated with corporate governance recommendations is to create the framework and guidelines on which the company runs its operations, if it is to fulfill its competitiveness requirements and increase its market value.…”
Section: Relevant Previous Researchmentioning
confidence: 99%
“…According to the research of Luo et al (2016) which explained that to identify high-quality companies and lowquality companies were 92.16 percent and 93.75 percent, respectively, which indicated that the model has realized good predictions. While research on Wierzbicka (2018) with her research about these elements, they included corporate governance mechanisms. The basic role associated with corporate governance recommendations is to create the framework and guidelines on which the company runs its operations, if it is to fulfill its competitiveness requirements and increase its market value.…”
Section: Relevant Previous Researchmentioning
confidence: 99%